ANALISIS PEMBATASAN MASA JABATAN KETUA UMUM PARTAI POLITIK DALAM MENDUKUNG DEMOKRASI DI INDONESIA - NIM. A1011211248, LISTANIA ADELLA (Jurnal Fatwa Hukum, 2025)
AbstractPolitical parties are one of the important elements in a democratic system, therefore, political parties need democratization in the internal implementation of political parties. One important aspect in the implementation of democratic values within political parties is the need to limit the term of office of the general chairman of political parties. This study aims to analyze the limitation of the term of office of the General Chairperson of Political Parties in supporting democracy in Indonesia. The limitation of the term of office of the General Chairperson is an important issue in the context of leadership rotation and strengthening internal democracy in political parties. This study uses a type of research in the form of juridical-normative with a qualitative method in the form of an analytical descriptive approach, which combines literature studies and analysis of related documents, such as political party laws and regulations related to term limits. The data collected were then analyzed using democratic theory and leadership regeneration theory. The results of the study indicate that limiting the term of office of the General Chairperson can strengthen the democratic system in political parties by encouraging leadership rotation, preventing centralization of power and political dynasties, and increasing member participation in decision making. The recommendation given is that there needs to be a more assertive and clear regulation regarding the term limits of the general chairperson of political parties and the mechanism for changing management in the law in order to create legal certainty.  Keywords: Term Limits, General Chair of Political Parties, Democracy  AbstrakPartai politik merupakan salah satu elemen penting dalam sistem demokrasi, oleh karena itu dalam partai politik diperlukan suatu demokratisasi pada implementasi internal partai politik. Salah satu aspek yang penting dalam implementasi nilai demokrasi pada internal partai politik ialah mengenai perlunya pembatasan masa jabatan ketua umum partai politik. Penelitian ini bertujuan untuk menganalisis pembatasan masa jabatan Ketua Umum Partai Politik dalam mendukung demokrasi di Indonesia. Pembatasan masa jabatan Ketua Umum menjadi isu penting dalam konteks rotasi kepemimpinan dan memperkuat demokrasi internal partai politik. Penelitian ini menggunakan jenis penelitian berupa yuridis-normatif dengan metode kualitatif berupa pendekatan deskriptif analitis, yang menggabungkan studi pustaka dan analisis dokumen terkait, seperti undang-undang partai politik dan peraturan terkait pembatasan masa jabatan. Data yang dikumpulkan kemudian dianalisis menggunakan teori demokrasi dan teori regenerasi kepemimpinan. Hasil penelitian menunjukkan bahwa pembatasan masa jabatan Ketua Umum dapat memperkuat sistem demokrasi di partai politik dengan mendorong rotasi kepemimpinan dapat mencegah sentralisasi kekuasaan dan dinasti politik, serta meningkatkan partisipasi anggota dalam pengambilan keputusan. Rekomendasi yang diberikan adalah perlu adanya pengaturan yang lebih tegas dan jelas mengenai batasan masa jabatan ketua umum partai politik dan mekanisme pergantian kepengurusan dalam undang-undang agar terciptanya kepastian hukum.Kata Kunci: Pembatasan Masa Jabatan, Ketua Umum Partai Politik, Demokrasi.